A Strategic Program for Risk Assessment and Intervention to Mitigate Environmental Stressor-Related Adverse Pregnancy Outcomes in the Indian Population - Jain, Divyanu; Jain, Ajay K.; Metz, Gerlinde A. S.; Ballanyi, Nina; Sood, Abha; Linder, Rupert; Olson, David M. (Frontiers in Reproductive Health, 2021)
Global environmental stressors of human health include, but are not limited to, conflict, migration, war, natural disasters, climate change, pollution, trauma, and pandemics. In combination with other factors, these stressors influence physical and mental as well as reproductive health. Maternal stress is a known factor for adverse pregnancy outcomes such as preterm birth (PTB); however, environmental stressors are less well-understood in this context and the problem is relatively under-researched. Considering the seriousness of this problem, an international and interdisciplinary group of researchers, physicians, and organizations dedicated to the welfare of women at risk of adverse pregnancy outcomes launched an international program named Optimal Pregnancy Environment Risk Assessment (OPERA). The program has been supported by the Worldwide Universities Network, World Health Organization and March of Dimes USA. OPERA aims to discover and disseminate inexpensive, accessible tools to diagnose women at risk for PTB and other adverse pregnancy outcomes as early as possible and to promote effective interventions to mitigate these risks. This review article addresses the influence of environmental stressors on maternal-fetal health and describes the role of OPERA in helping local practitioners by sharing with them latest risk prediction and mitigation tools. The consequences of these stressors can be partially mitigated by experience-based interventions that build resilience and break the cycle of inter-and-transgenerational transmission. The shared knowledge and experience from this collaboration will guide, and facilitate efforts at local level especially in developing countries like India to develop strategies appropriate for the jurisdiction for improving pregnancy outcomes in vulnerable populations.